â€œBRTTâ€ (Clean, Neat, Orderly, Organized) Program as a Pioneer of Daarut Tauhid Santri with Ecological Intelligence - Mutiara, Dea (Universitas Pendidikan Indonesia, 2020)
Daarut Tauhid as one of the educational institutions that study religion proves that an islamic boarding school does not only deepen the Holy Qurâ€™an and hadith; but also does real activities in the society. Researchers are interested in capturing the process of implementing the